The Chemical Characteristics of Water Soluble Polysaccharides Extract from Sprouted Gembili (Dioscorea esculenta) Tuber - Harijono, Harijono; Sunarharum, Wenny Bekti; Rakhmita, Isna Suci (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Gembili contains water-soluble polysaccharides (WSP) besides other components such as starch, fiber, protein, and other carbohydrate. The suitable method should be developed to separate WSP from other components such as protein that bound tightly. It is supposed that limited sprouting could be separate WSP more easily, due to hydrolysis of some major components in gembili tuber. The objective of this research was to elucidate the effect of sprouting time on the characteristics of gembili WSP. This research used Completely Randomized Design with 5 levels (sprouting time of 6, 12, 18, 24, 30 days). The results showed that sprouting time affected water, amylose, crude fiber, protein content, and yield extracted WSP. The analysis of precipitate in centrifugation to separate starch from filtrate in WSP extraction process, showed that sprouting time affected total sugars, reducing sugars, amylose, and crude fiber content of precipitates.Keywords: gembili, sprouting time, water soluble polysaccharides